ANALISIS FAKTOR KESULITAN BELAJAR SISWA PADA MATERI POKOK SISTEM EKSKRESI MANUSIA KELAS XI MIA SMA NEGERI 16 MEDAN - Rahmayani Rahmayani; Masdiana Sinambela; Rosida Rosida (Jurnal Pelita Pendidikan, 2017)
The objective of this research is to know the student’s learning difficulties in the material of SystemHuman's Excretion from indicator aspects and factors students learning difficulties on the System Human'sExcretion class XI MIA in SMA Negeri 16 Medan year learning 2016/2017. The research design used is descriptivequantitative. Samples was taken by Purposive Sampling which amounts 80 students. Data colletion techniquesused were test and questionnaire. The results of research showed that students were categorized as incomplete.Presentation of student learning difficulties on aspects of learning indicators that are indicators-1 of 52.81% in thecategory of very high difficulty, in indicator-2 of 55.41% in the very high difficulty category, in indicator -3 of 64% inthe category of very high difficulty, in indicator-4 of 52.25% in the category of very high difficulty, in indicator-5 of40.625% in high difficulty category, on indicator-6 of 50.41% is in the category of very high difficulty. The factorsthat cause student learning difficulties in studying the subject matter of human excretion system are health,student attention, interest, motivation, learning standard, subject matter, parent and school atmosphere,intelligence, teacher teaching method and media.Keywords: factor learning difficulties, learning Indicators, learning difficulties